2-Deoxy-D-Glucose: Chemistry and Biology - Singh, Raman; Kumar, Antresh; Singh, Kuldeep (Bentham Science Publishers, 2024)
2-Deoxy-D-Glucose: Chemistry and Biology extensively examine 2-deoxy-D-glucose (2DG), a glucose analog with profound biomedical and therapeutic potential. This detailed resource covers 2DG's chemical structure, methods of synthesis, and its pivotal roles in diagnostics and therapeutics. This book provides a comprehensive overview of the compound’s multifaceted uses, from antiviral applications to its emerging role in cancer treatment.Key Features:- Comprehensive coverage of 2DG synthesis, structure, and characterization.- Insights into 2DG's diagnostic and therapeutic potential, including cancer and antiviral applications.- Exploration of its role in the Warburg effect and glycosylation inhibition.- Discussion on 2DG's clinical applications, including COVID-19 treatments.